BENTUK PERLINDUNGAN HUKUM BAGI KONSUMEN MOBIL SEMI-AUTONOMOUS TERHADAP KECELAKAAN AKIBAT GAGALNYA SISTEM - Kevin Bryan Arya Herwanto; Rosalinda Elisina Latumahina (Gapenas Publisher, 2023)
The increasing number of semi-autonomous vehicles on the streets of Indonesia, plus the absence of a legal rule governing the legality of these vehicles, poses a new legal problem. The problem arises if there is an accident caused by the failure of the semi-Autonomous system who should be responsible and what is the form of legal protection obtained by a consumer who uses the vehicle, this research is normative juridical research in which the author uses the method of statutory approach and also normative research. The results of this study found that currently the position of semi-autonomous cars can be said to be objects that have AI (Artificial Intelligence) technology where the position of AI in Indonesia itself is included in the shutter of Electronic Agents or Electronic Systems, and the provisions regarding these rules have been regulated in the ITE Law and PP 71/2019 which means that business actors must be responsible for the existence of the system. Consumers themselves get legal protection in accordance with what has been stated in Law No. 8 of 1999 concerning Consumer Protection and consumers are entitled to compensation for losses suffered by consumers